2002
DOI: 10.1093/ije/31.6.1208
|View full text |Cite
|
Sign up to set email alerts
|

Social networks and mortality based on the Komo-Ise cohort study in Japan

Abstract: This study provides evidence that social networks are an important predictor of mortality risk for middle-aged and elderly Japanese men and women. Lack of participation, for men, and being single and lack of meeting close relatives, for women, were independent risk factors for mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(66 citation statements)
references
References 23 publications
2
62
0
2
Order By: Relevance
“…18 In the WHAS studies, previously established criteria were used to stratify women into 1 of 3 tertiles 15 of disability. 19 WHAS I enrolled women aged 65 years and older who were in the most disabled tertile among the community-dwelling population (Nϭ1002). In contrast, WHAS II enrolled women ages 70 to 79 years who were in the 2 least disabled tertiles (Nϭ436).…”
Section: Women's Health and Aging Studiesmentioning
confidence: 99%
“…18 In the WHAS studies, previously established criteria were used to stratify women into 1 of 3 tertiles 15 of disability. 19 WHAS I enrolled women aged 65 years and older who were in the most disabled tertile among the community-dwelling population (Nϭ1002). In contrast, WHAS II enrolled women ages 70 to 79 years who were in the 2 least disabled tertiles (Nϭ436).…”
Section: Women's Health and Aging Studiesmentioning
confidence: 99%
“…37,38,39,40 Social networks are an important predictor of mortality risk for middle-aged and elderly Japanese men and women. 37 Welin, et al 38,39 reported that high levels of social, home, and outside home activities protected middle-aged men from premature death. Reynolds, et al 40 , reported that socially isolated women were at a significantly elevated risk of cancer mortality.…”
Section: Stratified Analysis By Study Areamentioning
confidence: 99%
“…With notable exceptions there is little evidence beyond the western world, where JudeoChristian traditions are strong, despite differences in the ways in which religion is structured (Iwasaki et al 2002;Krause et al 1999Krause et al , 2002Yeager et al 2006;Zhang 2008). This study adds several important elements to our understanding of this association.…”
Section: Discussionmentioning
confidence: 99%
“…Religious activity has been empirically linked to an array of attributes that impact upon health outcomes, such as personal values, locus of control, feelings of self, health related behaviors, intergenerational associations, and coping mechanisms (Ellison and Levin 1998;Gillum 2006;Hill et al 2007;Hummer et al 1999Hummer et al , 2004Iwasaki et al 2002;Krause 2004Krause , 2002Krause et al 2002;Lawler-Row and Elliott 2009;Obisesan et al 2006;Ryan and Willits 2007;Strawbridge et al 2001). This research has provided good evidence that strong religious convictions, especially when combined with frequent attendance of religious services, results in longer and functionally healthier lives (Chida et al 2009;Gillum et al 2008;Hummer et al 1999;Helm et al 2000;Hill et al 2005;Idler and Kasl 1997;Kelley-Moore and Ferraro 2001;Koenig et al 1999;Krause et al 1999;La Cour et al 2006;Oman and Reed 1998;Roff et al 2006;Strawbridge et al 1997;Yeager et al 2006;Zhang 2008).…”
Section: Introductionmentioning
confidence: 99%